2016
DOI: 10.1371/journal.pone.0167533
|View full text |Cite
|
Sign up to set email alerts
|

Functional Morphology of the Arm Spine Joint and Adjacent Structures of the Brittlestar Ophiocomina nigra (Echinodermata: Ophiuroidea)

Abstract: The skeletal morphology of the arm spine joint of the brittlestar Ophiocomina nigra was examined by scanning electron microscopy and the associated epidermis, connective tissue structures, juxtaligamental system and muscle by optical and transmission electron microscopy. The behaviour of spines in living animals was observed and two experiments were conducted to establish if the spine ligament is mutable collagenous tissue: these determined (1) if animals could detach spines to which plastic tags had been atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 77 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…Most notably, in both classes, we found the presence of spine nerves spreading all along the shaft of the spines and that are innervated by lateral nerves emanating from the radial nerve cords. In ophiuroids, spine nerves are also present, and they are similarly innervated by peripheral nerves protruding from the radial nerve cords (Wilkie, 2016; Zueva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, in both classes, we found the presence of spine nerves spreading all along the shaft of the spines and that are innervated by lateral nerves emanating from the radial nerve cords. In ophiuroids, spine nerves are also present, and they are similarly innervated by peripheral nerves protruding from the radial nerve cords (Wilkie, 2016; Zueva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The brittle star is an echinoderm that possesses several skeletal parts 17 , including lenses, spicules, teeth, and arm vertebrae, which, respectively, serve its visual system 5 , locomotor system, oral system, and act as joints 18 . A study of the lens nanostructure showed that each lens comprises a single crystal composed of two coherent Mg-calcite phases: a phase comprising nanoparticles of high-Mg calcite (~5 nm diameter, ~40 mol% MgCO 3 ), coherently incorporated in a phase consisting of a poorer Mg-calcite matrix (~13 mol% MgCO 3 ) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This study paid particular attention to the structure of these cells and their transformation during the regeneration process. Until now it was believed that JLCs are a specific type of neurosecretory-like cells characteristic of echinoderms, the function of which is to alter the mechanical properties of connective tissue [ 43 , 44 , 61 66 ]. A characteristic feature of JLCs is the presence in their cytoplasm of electron-dense granules whose largest dimension varies between species but is within the range 0.1–0.85 μm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a neuropeptide, referred to as somatostatin, has been detected in them [ 48 ]. In this regard, they are now considered to be a special type of neurosecretory neuron [ 66 ] and, accordingly, may have an ectodermal origin. Thus, the transdifferentiation of ectodermal (nerve) cells into endodermal ones occurs during regeneration of the visceral mass in H .…”
Section: Discussionmentioning
confidence: 99%